ANALYSIS OF SERVICE QUALITY AND TRUST ON CONSUMER LOYALTY WITH SATISFACTION AS AN INTERVENING VARIABLE (CASE STUDY OF P.O BORLINDO) - Abdul Razak Sabara; Otto Randa Payangan; Muhammad Ismail (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2020)
This research aims to determine the effect of service quality and trust on the consumers' loyalty through consumer satisfaction directly and indirectly. The research was conducted at PO Borlindo by taking passengers as a research object. This research draft uses quantitative descriptive research with direct observation in the field. Research data form primary and secondary data from the company. Data is processed and analyzed by path analysis methods with IBM-SPSS. The results showed that the Service quality and trust positively affect consumer satisfaction and consumer loyalty directly. Trust had a positive effect on consumers' loyalty through consumer satisfaction. The hypothesis testing shows that the service quality variable is the variable with the lowest level of influence among other variables on consumer loyalty at PO Borlindo.